Academic Stress and Coping Strategy Among The Final Year Of Nursing Students’ In Banten Province - Maria Windi Jemadu; Conny Rapita Ompusunggu; Eka Putri Gracella Komigi; Veronica Paula; Mega Sampe Padang (Jurnal Pustaka Medika (Pusat Akses Kajian Medis dan Kesehatan Masyarakat), 2023)
Background: Academic stress is an unavoidable part when facing pressures that arise from academic assignments as nursing students need to meet their abilities both in terms of knowledge and practical skills in hospitals. Nursing students can use appropriate coping strategies to overcome academic stress. Purpose: The purpose of this study was to determine academic stress and coping strategies for final-year nursing students in Banten Province. Methods: This study used a quantitative method with a descriptive approach and univariate analysis. The population of this research is the final year students in Banten Province as many as 3693 students and the sample is 361 respondents. The research respondents were final-year nursing students in Banten Province obtained with a purposive sampling technique. The instrument used was a Modified Academic Stress Questionnaire and Ways of Coping, the instrument was reliable and valid (Cronbach alpha 0,851 and 0,779). Results: The result of the study are students who experienced mild stress 146 students (40.4%), moderate stress 115 students (31.9%), normal stress 53 students (14.7%), and severe stress 47 students (13.0%). The coping strategies used are Problem-Focused Coping for 291 students (80.6%), Emotional-Focused Coping for 59 students (16.3%), and using both strategies simultaneously for 11 students (3.0%). Conclusions: Academic stress occurs in every student in response to the academic demands they have. It is hoped that the selection of coping strategies for each nursing student can help to deal with the stress experienced. Students need to find effective coping strategies which can be done to deal with stress such as sharing with other people, doing hobbies, and doing self-reflection.